Nanostructured carbon adsorbents for haemoperfusion - Akhmetova, A. S.; Saliev, T.; Nurgozhin, T.S.; Mikhalovsky, S. V. (Nazarbayev University, 2013)
500 million persons live with various kidney diseases. Chronic illness of kidneys eventually leads to the terminal stage known as end stage renal disease (ESRD). Dialysis is a life sustaining therapy for patients who progress to ESRD and do not receive a transplant. There are over one million ESRD patients on dialysis worldwide. Despite the relatively high cost of dialysis ($55,000 per patient per year) patient survival remains poor. Current dialysis systems remove small, water soluble metabolites but fail to remove significant amounts of higher molecular weight and protein bound uraemic toxins whose retention is most damaging. In this project an alternative extracorporeal treatment using adsorption as the main clearing process, is being developed.
Keywords: first research week; end stage renal disease; healthcare problems